2011
DOI: 10.1093/brain/awr130
|View full text |Cite
|
Sign up to set email alerts
|

Similar amyloid-β burden in posterior cortical atrophy and Alzheimer's disease

Abstract: While the clinical presentation of posterior cortical atrophy is clearly distinct from typical Alzheimer's disease, neuropathological studies have suggested that most patients with posterior cortical atrophy have Alzheimer's disease with an atypical visual presentation. We analysed in vivo pathophysiological markers of Alzheimer's disease such as cerebrospinal fluid biomarkers and positron emission tomography imaging with ¹¹C-labelled Pittsburgh compound-B in posterior cortical atrophy to determine whether bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
73
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 34 publications
10
73
1
1
Order By: Relevance
“…Previous studies from our group and others using amyloid PET have shown that the distribution of fibrillar amyloid in AD is largely overlapping and is indistinguishable across clinical variants (26,(50)(51)(52)(53). This raises the possibility that network-based degeneration may be driven by other factors, such as oligomeric Aβ (not imaged by current PET ligands) or neurofibrillary tangles.…”
Section: Discussionmentioning
confidence: 90%
“…Previous studies from our group and others using amyloid PET have shown that the distribution of fibrillar amyloid in AD is largely overlapping and is indistinguishable across clinical variants (26,(50)(51)(52)(53). This raises the possibility that network-based degeneration may be driven by other factors, such as oligomeric Aβ (not imaged by current PET ligands) or neurofibrillary tangles.…”
Section: Discussionmentioning
confidence: 90%
“…15 Patients with PCA likewise show diffuse PiB retention. 23,24 As with other focal variants of AD, areas of hypometabolism correlate strongly with the focal symptoms, 3,4,18,24 as neurofibrillary tangles may have a strong contribution to the clinical features. 23 In fact, most AD patients presenting with aphasia have an asymmetrical increase in left hemispheric neurofibrillary tangle density as compared to typical AD patients.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies on CSF biomarkers in distinct clinical variants of probable AD have shown that CSF Aβ 42 levels are reduced (reflecting greater amyloid burden) independent of phenotype (Baumann, et al, 2010, Bouwman, et al, 2009, Coppi, et al, 2014, de Souza, et al, 2011a, de Souza, et al, 2011b, Magnin, et al, 2014, Santangelo, et al, 2014, Seguin, et al, 2011, Teng, et al, 2014). In contrast, for CSF t-tau and p-tau results have shown discrepancies between studies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, for CSF t-tau and p-tau results have shown discrepancies between studies. Some studies have found comparable t-tau and p-tau levels between amnestic AD and PCA (Baumann, et al, 2010, Coppi, et al, 2014, de Souza, et al, 2011a, de Souza, et al, 2011b, Seguin, et al, 2011), amnestic AD and lvPPA (Santangelo, et al, 2014, Teng, et al, 2014), and between EOAD and LOAD (Bouwman, et al, 2009). One study found lower CSF t-tau and p-tau levels in PCA than in lvPPA and amnestic AD (Teng, et al, 2014) and another study found higher CSF t-tau and p-tau levels in lvPPA compared to amnestic AD (Magnin, et al, 2014).…”
Section: Introductionmentioning
confidence: 99%